Structure, Composition, Carbon Stocks of Dipterocarpaceae in West Batang Toru Forest Block, North Tapanuli Regency, North Sumatra - Pratiwi, Suci; Pasaribu, Nursahara; Julius Paolo Siregar (Talenta Publisher, 2024)
The West Batang Toru Forest Block in the North Tapanuli Regency, North Sumatra, is one of the lowland forests in Sumatra with a variety of plant communities and populations that have not been fully documented. This area is considered a potential high-value carbon reserve of ecological significance. The purpose of the study was to determine the structure and composition of the Dipterocarpaceae at the West Batang Toru Forest Block. This research was conducted from September 2021 to March 2022. The research location was determined by using the purposive sampling method with a transect length of 300 m. Each lane had plots of 20 Ã— 20 m measured in a zigzag position and had an interval of 10 meters. The number of plots in each lane was 10, for a total of 90 plots. Based on the observations, there were nine species of Dipterocarpaceae obtained from a total of 621 individuals. The basal area ranged from 578.02 cm2/Ha to 397,894.43 cm2/Ha, and the largest basal area was at the tree level. The vegetation composition ranged from 60% to 66%, and the highest composition was at tree level. Sixty-two trees were classified as having the largest basal area, followed by poles (42 individuals) and saplings (64 individuals). Shorea platyclados occurred consistently with a compositional percentage value at the tree level with a value of 66%, the pole level of 53%, the sapling rate of 34%, and the seedling level of 9%. The carbon stocks from Dipterocarpaceae stands were 91534 tons/ha, which is the first estimate of their ecological importance